2017
DOI: 10.1016/j.pvr.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotype-specific concordance between EuroArray HPV, Anyplex II HPV28 and Linear Array HPV Genotyping test in Australian cervical samples

Abstract: PurposeTo compare human papillomavirus genotype-specific performance of two genotyping assays, Anyplex II HPV28 (Seegene) and EuroArray HPV (EuroImmun), with Linear Array HPV (Roche).MethodsDNA extracted from clinican-collected cervical brush specimens in PreservCyt medium (Hologic), from 403 women undergoing management for detected cytological abnormalities, was tested on the three assays. Genotype-specific agreement were assessed by Cohen's kappa statistic and Fisher's z-test of significance between proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 37 publications
5
33
1
Order By: Relevance
“…In a recent study, Cornall et al(2016) demonstrated that clinical sensitivity and specificity of EUROArray HPV was similar to a number of HPV tests including HC2 [18] and was non-inferior to HC2 in terms of sensitivity. However, that study focussed on a disease-enriched population of 404 women of which 336 had CIN2+.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent study, Cornall et al(2016) demonstrated that clinical sensitivity and specificity of EUROArray HPV was similar to a number of HPV tests including HC2 [18] and was non-inferior to HC2 in terms of sensitivity. However, that study focussed on a disease-enriched population of 404 women of which 336 had CIN2+.…”
Section: Discussionmentioning
confidence: 96%
“…EUROArray HPV enables the simultaneous detection of 30 different anogenital HPVs in a single reaction through the PCR amplification of fragments of E6 and E7 viral oncogenes. As EUROArray HPV is a relatively novel test, few data have been published regarding its clinical performance [18] and none where performance has been related to the Meijer 2009 criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Anyplex28 assay and validated DNA extraction protocol (STARlet) is designed to detect HPV DNA at a sensitivity and specificity threshold to predict grade II cervical intraepithelial neoplasia or greater from female cervical samples. However, HPV DNA detection and genotyping is also vital to monitor the effectiveness of vaccination programmes in the community, requiring assays that detect all HPV DNA from a sample (Cornall et al 2017). The findings presented suggest that the laboratory standard extraction protocol (5-fold increase in sample input) utilizing the Anyplex28 genotyping kit could be considered for research where higher analytical sensitivity is desired, such as in studies of HPV vaccine impact and effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Different detection method technologies are applied to tissue HPV genotypes analysis, but there is no Food and Drug Administration approved molecular tests to detect HPV infection in HNSCC [12][13][14][15]. There are 193 distinct molecular tests that are commercially available on the global market for the detection of HPV in cervical specimens.…”
Section: Introductionmentioning
confidence: 99%